12. CURRENT STATUS AND DEMAND OF OBSTETRICIANSGYNECOLOGISTS WORKING IN PROVINCIAL AND DISTRICT HOSPITALS IN VIETNAM ECOLOGICAL REGIONS (Vietnam Journal of Community Medicine, 2023)
Background: Obstetric health care was always an important problem in countries where humanresources are decisive. The research carried out was the basis of innovation and training for obstetricalhuman resources, meeting people’s needs.Objectives: Describe the current situation and needs of obstetricians working at provincial anddistrict hospitals in representative ecological regions in Vietnam.Methods: A cross-sectional descriptive study in 7 provinces/cities, including 27 hospitals.Results: The situation and demand for human resources specialized in obstetrics and gynecologywere mostly in the Red River Delta (>40%), mainly at the provincial level (>54%). By 2025, theCentral Coast and South Central region will have the highest demand for human resources forobstetricians (from 15.5% in 2020 to 30.3%). The Obstetrician-Gynecologist’s human resources arestill lacking in number, causing overcrowding. The need for specialized training support in technicalknowledge and skills, procedures and surgery is closely related to the local situation.Conclusion: The situation and demand for obstetrical human resources in 2020-2025 are concentratedin the Red River Delta at provincial hospitals. The number of obstetrician human resources has notbeen able to fully and promptly respond to patients. However, the quality of staff is guaranteed, andthe capacity is enough to meet the service.
Keywords: Human resource situation, human resource needs, demand for doctors, obstetricians, gynecologists.